Jorgensen’s dilema: the quest for semantic foundations of imperatives - León Untiveros, Miguel A. (2016)
In this paper we attack horn 2 of the Jørgensen’s dilemma (prohibitive thesis), so we enforce horn1 (permissive thesis). Also, we explore partially the idea of a syntactical solution for a logic of imperatives based on the fact of the lack of truth value of imperatives.